Mäerl calcification, photosynthesis and respiration in an acidified ocean - Nieves, Laura Sordo de las (2017)
With the increase of atmospheric CO2 and the associated acidification of the oceans, rhodolith (mäerl) beds are under severe threat. The general lack of consensus regarding the foreseeable effects of Ocean Acidification (OA) on coralline algae is largely due to the divergences of results obtained in different scientific experiments. These divergences may be related to differences in temperature, irradiance, CO2 levels, time of exposure and also on technical difficulties concerning the experimental methodologies used. This thesis aimed to determine the photosynthesis, calcification and respiration rates of the mäerl species Phymatolithon lusitanicum under natural conditions in Southern Portugal and to assess the effect that ocean acidification will have on these processes under different irradiances, temperatures, CO2 concentrations and times of exposure. Dark respiration and photosynthesis increased with temperature in summer and spring and decreased in winter and autumn while calcification rates did not change seasonally. A direct CO2 control system was developed and found to be reliable to assess the short and long term effect of OA on coralline algae. In the short term, photosynthesis and calcification increased with CO2 and temperature, but after prolonged exposure this pattern was reversed and algae exposed to high CO2 showed lower photosynthetic and calcification rates and accumulated growth with respect to control algae, effects that were enhanced with increasing irradiances. Dark respiration was unaffected by CO2 but increased with temperature. The results suggest that temperature, irradiance, CO2 level and time of exposure are determinant factors in ocean acidification experiments with coralline algae. Both temperature and high light intensified the effect of high CO2 on Phymatolithon lusitanicum and these will be determinant factors on the long-term resilience of Lusitanian rhodolith beds to OA. Face ao aumento do CO2 atmosférico e consequente acidificação dos oceanos os bancos de rodolitos (mäerl) ...